The process of nursing a child with Haddad syndrome - Kołodziejska, Aneta; Kołodzeike, Dominika; Małecka-Dubiela, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2020)
Haddad syndrome is a combination of congenital central hypoventilation and Hirschsprung’s disease. This disease is very rare and caus-es mainly sleep apnoea and problems with intestinal peristalsis. Haddad syndrome is characterised by hereditary disorders of the auto-nomic nervous system and the lack of nerve ganglia in the distal part of the large intestine. The purpose of the above work is to illustrate the role of the nurse in caring for a child with Haddad syndrome and to present diagnoses and interventions based on the ICNP terminology, which the staff should include in the treatment process. In this work the method of literature analysis as well as the individual case was used. It was also based on interview, observation, and interpretation of the patient’s medical records. The study was conducted in September 2018 during a home visit as part of nursing care for a mechanically ventilated patient. The patient was diagnosed. Eight nursing diagnoses were formulated. These included: apnoea, impaired airway patency, abdominal pain, weakness, underweight, disturbed sleep, lack of appetite, and fatigue. The International Classification of Nursing Practice ICNP® is a huge source of terms that facilitate, speedup, and make the nurse’s work more effective. It enables the documenting and describing of specific diagnoses, interventions, and results selected and applied to them [6]. The use of an appropriate diet and pharmacotherapy proved to be effective, which improved the patient’s condition and allowed her to return to normal functioning.